2012
DOI: 10.1111/j.1460-2466.2012.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion, Motivation, and the Persuasive Effects of Message Framing

Abstract: This study explored the effects of premessage emotions (happiness, anger, and fear) and chronic levels of motivational system activation (behavioral approach system: BAS, and behavioral inhibition system: BIS) on the processing of gain‐ and loss‐framed persuasive messages. The data showed that emotion functions (approach and avoidance), not valences (positive and negative), predicted emotions' interactions with motivational systems and framed messages. While fear was associated with BIS, happiness and anger we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…The popularity of the morality frame, in turn, was explained by some participants from an impression‐management motivation, with users trying to communicate a specific identity to others. These results are consistent with another strand of framing theory, which connects the effects of message frames to specific motivations (e.g., Yan, Dillard, & Shen, ). Thus, in addition to—or, perhaps, in combination with—producing specific emotional responses, frames may activate specific motivations related to news sharing.…”
Section: Discussionsupporting
confidence: 89%
“…The popularity of the morality frame, in turn, was explained by some participants from an impression‐management motivation, with users trying to communicate a specific identity to others. These results are consistent with another strand of framing theory, which connects the effects of message frames to specific motivations (e.g., Yan, Dillard, & Shen, ). Thus, in addition to—or, perhaps, in combination with—producing specific emotional responses, frames may activate specific motivations related to news sharing.…”
Section: Discussionsupporting
confidence: 89%
“…Recent work by Yan, Dillard, and Shen (2012) has shown that emotional stimuli can activate the approach and avoidance system and that these changes in approach and avoidance activity in turn moderate the effects of framed messages. In fact, there may be several factors that can influence the effects of message framing through their effects on the approach and avoidance systems (Yan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Yan, Dillard, and Shen (2012) has shown that emotional stimuli can activate the approach and avoidance system and that these changes in approach and avoidance activity in turn moderate the effects of framed messages. In fact, there may be several factors that can influence the effects of message framing through their effects on the approach and avoidance systems (Yan et al, 2012). As Rothman and colleagues (2006) have pointed out, investigating the extent to which factors external to the message can influence recipients’ approach and avoidance systems and thereby the effectiveness of gain- and loss-framed messages is a particularly promising avenue for message framing research.…”
Section: Discussionmentioning
confidence: 99%
“…While we distinguished among political ideology and candidate preference, this study has for example not analyzed differences in psychological characteristics of users. Research in the field of message framing has shown that people's motivations are subject to individual variations that will cause them to experience emotionally evocative message as a function of those individual differences (Yan, Dillard, & Shen, 2012). Second, while we controlled for the initial condition of videos on YouTube, we did include a separate control group in this analysis.…”
Section: Discussionmentioning
confidence: 99%